ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM DENGAN PENDEKATAN OPTIMISASI MULTIOBJEKTIF UNTUK PENGUKURAN VALUE AT RISK - Fiki Farkhati; Abdul Hoyyi; Yuciana Wilandari (Jurnal Gaussian, 2014)
Mean Variance Efficient Portfolio (MVEP) is theory of portfolio which purposed to standard investor  because approach has only one objective that minimize portfolio risk. Portfolio with multi-objective optimization that simultaneously maximize portfolio return and minimize portfolio risk with various weighting coefficient k represents risk aversion index. The purpose of this research is analyze proportion each stock in order that is formed optimal portfolio approach multi-objective optimization and analyze expected return and risk that suitable with preference investor. This research is based on cases stocks ASII, TLKM, SMGR, UNVR and LPKR. As a specific example investment Rp 50.000.000,00 in 20 days with 95% degree of confidence. Optimal portfolio for risk seeker investor is portfolio with     k = 0,01 with expected profit Rp 1.547.392,00 and risk estimation Rp 33.832.562,00. Optimal portfolio for risk indifference investor is portfolio with 1 ≤ k ≤ 100 with expected profit                Rp 965.678,00 until Rp 1.435.038,00 and risk estimation Rp 19.500.464,00 until                  Rp 25.513.351,00. Optimal portfolio for risk averse investor is portfolio with k = 10000 with expected return Rp 950.414,00 and risk estimation Rp 19.495.116,00.